A Response to the Findings of Jevne - Talley, William Martin (Canadian Journal of Counselling and Psychotherapy, 2012)
This brief response to the findings of Jevne ( 1981 ) on the competencies and issues in Canadian counsellor education is an attempt to determine some rationale for the findings and to raise questions as to why the respondents answered as they did.